From Bibliometrics to Altmetrics: Examining the Relationship Between Citation Count and Altmetric Score in Publications on Artificial Intelligence - Maatouk, Yasser (Journal of King Abdulaziz University: Computing and Information Technology Sciences, 2022)
In this research work, we studied two main research questions. First, we explored how artificial intelligence (AI) publications are seen on various altmetric platforms. Second, by looking at publications in the field of AI, we examined whether bibliometrics and altmetrics are correlated. For each of the 8000 AI publications on the Web of Science (WoS) database with altmetric scores, we recorded the citation counts and altmetric scores. Pearson’s correlation for the two lists of variables was found to be 0.2. This result is near to zero, indicating that there is weak correlation between citations and altmetric attention score. Further, in the two top lists of publications according to citation count and altmetric score, respectively, we found only one paper in common. For the time being, altmetric scores are weakly correlated with citation in the AI publications. In terms of research impact, altmetrics should be regarded as complementary to traditional bibliometrics rather than as a replacement measure. Beside these results, this article gives an overview of this area of research (scientometrics and informetrics). All related terminologies are defined, and for the purpose of this study we focus on bibliometrics and altmetrics.